LANDASAN BIMBINGAN DAN KONSELING DALAM MENGHADAPI BERBAGAI LINTAS BUDAYA - Agus Basuki Basuki (Paradigma, 2012)
Guidance and counseling is an integral part of theeducation that have objects of human behavior. Humanbehavior in the context of social interaction can never beseparated from the social environment that involves the variouscomponents. One such component is the culture. Students arehighly influenced by the culture of the parents, preschool, andschool vary greatly in terms of the extent to which the childrenare encouraged to develop long-term relationships with peersand teachers outside the family.Various elements in the areas of people's lives is the seeds thatcould enrich the culture to build a strong community, butinstead can weaken the strength of the nation with varioussquabbles and disputes. Therefore the social relations necessaryto arrange to run centripetal, disagreements, disputes must beaddressed not by dogmatic attitude but with rational criticalattitude. Rational critical attitude can be done througheducation, because education is a strategic component whichhas an important role in determining the forward movement ofthe nationKey words : Guidance and counseling, education, students